Scientific and technological regimes in nanotechnology: Combinatorial inventors and performance - Andrea Bonaccorsi; Grid Thoma (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2005)
Academics and policy makers are questioning about the relation between science and technology in the emerging field of nano science and technology (NST) and the effectiveness of different institutional regimes. We analyze the performance of inventors in the NST using multiple indicators. We clustered patents in three groups according to the scientific curricula of the inventors. The first two groups are composed by patents whose inventors all are authors of at least one scientific publication in the NST or none of them have obtained a scientific publication in that field respectively. Thirdly, we isolated those patents that have at least one inventor, who is also author of at least one scientific publication in the NST. The underlining presumption of this classification is that of a proxy of different institutional complementarities of the inventive collective action in NST.
Keywords: 330; science-technology relation; emerging field; nanotechnology; patent quality; inventive productivity; Erfindung; Patent; Nanotechnologie